PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT ABADI MITRA TEKNOLOGI - Submission JORAPI; Julia Kumala Sari; Dede Andi (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of work motivation and work environment on employee performance at PT Abadi Mitra Teknologi. The research method used is a quantitative descriptive method. The population in this study was 80 employees with the sampling technique used, namely a saturated sample (census) so that respondents were obtained as many as 80 employees. Meanwhile, the primary data collection technique is through a questionnaire which is processed using the SPSS Version 25 application system. The data analysis methods used in this research are correlation analysis, regression analysis, determination analysis, t test and f test. Based on the results of the t test research, it was obtained that the t count for work motivation was t count 2.922 > t table 1.665. or significance 0.000 < 0.05, meaning that partially there is a significant influence of work motivation on employee performance. And the t calculated work environment is t calculated 6.816 > t table 1.665. or significance 0.000 < 0.05, meaning that partially there is a significant influence of the work environment on employee performance. For the f test, the calculated F is 23.191 > F table 3.115. or significance 0.000 < 0.05, meaning that simultaneously there is a significant influence of work motivation and work environment on employee performance. Multiple linear regression analysis obtained the equation Y = 13.957 + 0.063 (X1) + 0.627 (X2). Determination analysis obtained a value of 0.376 with a percentage of 37.6%, while the remaining 62.4% was influenced by other variables.